ANALISIS YURIDIS TINDAKAN SEPIHAK PENARIKAN PERWAKILAN DIPLOMATIK SUATU NEGARA DALAM KAIDAH HUKUM INTERNASIONAL (STUDI PERBANDINGAN ANTARA KASUS DUTA BESAR NORWEGIA UNTUK INDONESIA DAN DUTA BESAR JEPANG UNTUK KOREA SELATAN) - Syafariah Rizqa; Evi Deliana; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Article 43 of The 1961 Vienna Convention states that the termination requirements for diplomatic agent include the end of the function of diplomatic agent and persona non grata. In some cases, the termination of function of the Norwegian Ambassador to Indonesia that was withdrawn unilaterally was not caused by the provisions. Likewise, the case of unilateral withdrawal of the Japanese Ambassador to South Korea was occurred because of conflicts between the states. Problem was formulated about how international law regulates in relation to the withdrawal of a country's diplomatic representatives, what are factors which underlie these actions and how the appropriateness of the act of withdrawing diplomatic representatives with international law specifically regulates diplomatic relation. The purpose of this thesis is to find the answer to the problems.The type of conducted research is normative-juridical research by examining problems in terms of applicable principles of international law. In this study, the data sources used were secondary data with primary, secondary, and tertiary legal materials that carried out by means of library research.From the results of the study, it was found that, first, the unilateral withdrawal of diplomatic representation was not specifically regulated in international law, especially Vienna Convention but the practice was a discretionary act of state to protect its sovereignty. The act of withdrawing diplomatic representatives is not same as Persona Non Grata declaration, it also does not always lead to a break up of diplomatic relations, but it is also a dynamic in international relations which does not required the implementation of reciprocity principle. Second, the causes of the withdrawal of diplomatic representation may vary, it is not only limited as a form of protest against the policies of the receiving state, but also due to the actions and attitudes of the diplomatic representatives themselves. Third, this action has been part of customary international law so that it can be declared in accordance with the rules of international law.Keywords: Diplomatic Law- Diplomatic Representative -Withdrawal-Reciprocity-Persona Non Grata